2004
DOI: 10.1016/j.febslet.2004.10.112
|View full text |Cite
|
Sign up to set email alerts
|

Yeast two‐hybrid screens imply that GGNBP1, GGNBP2 and OAZ3 are potential interaction partners of testicular germ cell‐specific protein GGN1

Abstract: Gametogenetin (Ggn) is a testicular germ cell-specific gene specifically expressed from late pachytene spermatocytes through round spermatids. The function of gametogenetin protein 1 (GGN1) remains unknown. Here, we used the yeast twohybrid approach to look for more GGN1 interacting proteins. We found that gametogenetin binding protein 1 (GGNBP1), gametogenetin binding protein 2 (GGNBP2) and ornithine decarboxylase antizyme 3 (OAZ3) were potential GGN1 interaction partners. We determined the regions mediating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…It has been reported that GGNBP2 interacts with testicular proteins, GGN1, GGNBP1, CRISP2 and OAZ3 26, 28, 29, 30. Reciprocal immunoprecipitation (IP) with GGN (Figure 3A) and GGNBP2 (Figure 3B) antibodies demonstrated that GGN1 and GGNBP2 formed a protein complex in the testis.…”
Section: Resultsmentioning
confidence: 86%
“…It has been reported that GGNBP2 interacts with testicular proteins, GGN1, GGNBP1, CRISP2 and OAZ3 26, 28, 29, 30. Reciprocal immunoprecipitation (IP) with GGN (Figure 3A) and GGNBP2 (Figure 3B) antibodies demonstrated that GGN1 and GGNBP2 formed a protein complex in the testis.…”
Section: Resultsmentioning
confidence: 86%
“…9 Interestingly, the 7-Mb deletion carrier shared uncommon NF1 symptoms with the patient herein described (distinct craniofacial dysmorphisms, congenital heart defect, epileptic seizures, and severe mental retardation). 23 It is noteworthy that the deletion in the reported patient included a cluster of chemokine genes (CCL1, 2, 3,5,7,8,11,12,13,15,16,18, and 23) and four microRNA genes (hsa-mir-423, -193a, -365-2, and -632), deletion of which may contribute to the atypical phenotype. Interestingly, using a new literature-mining bioinformatics approach to prioritize disease genes, based on aGeneApart software, we identified NUFIP2 (nuclear fragile X mental retardation protein interacting protein 2; NM_020772) as a gene whose deregulation might be involved in the reported patient's mental retardation, being statistically associated with mental retardation in MEDLINE abstracts (Po10 À5 ).…”
Section: Discussionmentioning
confidence: 99%
“…12 While little experimental information exists, GGNBP2 could be involved in a process associated with spermatogenesis but might also have a tumor suppressive activity (GGNBP2 is also known as LCRG1 for laryngeal carcinoma-related gene 1). 13,14 As PIPOX and GGNBP2 have the same transcriptional orientation, we suspected the production of a chimeric transcript. We successfully amplified and sequenced this transcript in the propositus, with primers CHIMERIC-U/L designed to hybridize to PIPOX exon 4 and GGNBP2 exon 6, respectively (Figure 3b).…”
Section: Molecular Analysismentioning
confidence: 99%
“…Finally, several proteins identified in our yeast two-hybrid screen are involved in regulating cellular processes other than the actin cytoskeleton. Transmembrane emp24-like trafficking protein 10 (Tmed10) and gametogenetin-binding protein 2 (Ggnbp2) are involved in intracellular protein trafficking (72,83), whereas muscleblind-like RNA-binding proteins, such as muscleblind-like 3 (Mbnl3), inhibit muscle differentiation and regulate alternative splicing of pre-mRNA (25,38,69,74). Overall, the proteins identified in our screen regulate a number of highly ATP-dependent processes, which could require a localized source of ATP provided by CKB in muscle cells.…”
Section: Ckb Is Localized In Both Myocytes and Myotubesmentioning
confidence: 99%